Development of Patience and Sharing Character through Play Activities for Children Aged 3–4 Years - Ika Nur Indah; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to determine the effectiveness of play activities in developing the characters of patience and sharing among children aged 3–4 years at the Setia Hati Playgroup in Gawang. The background of this research is based on the importance of character education from an early age as a foundation for shaping children’s personalities. The research method used is Classroom Action Research (CAR) consisting of two cycles, each including planning, implementation, observation, and reflection. The research subjects consisted of 9 children. Data collection techniques were carried out through observation, documentation, and field notes. The results of the study show that group play activities, role-playing, and turn-taking games can improve children’s ability to demonstrate patient and sharing behaviors. The percentage of the development of patience increased from 45% in the pre-cycle to 82% in Cycle II, while the sharing character increased from 50% to 85%. Thus, play activities are effective in developing patience and sharing characters in early childhood.